Improving the efficiency of an electric drive with a cylindrical linear alternating current electronic engine - Dmitrii Andreevich Chirkov; Aleksandr Dmitrievich Korotayev; Evgenii Aleksandrovich Chabanov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Currently, linear motors find increasingly wide application in various industrial sectors. These motors feature a range of advantages including the absence of compound mechanical power transmissions between a motor and an actuator, simple design, and performance reliability. These advantages determine application of linear motors in electric drive systems of a range of industrial mechanisms including liquid metal and melt transfer units, various transport systems, and metal working and grinding machines. As an illustration, the article addresses submersible cylindrical linear alternating current electronic engines used for rodless oil extraction. Practice shows that the overall efficiency of such units is extremely low. This article is dedicated to the determination of performance and power/angle characteristics of such linear motors, their main energy indicators ???????????????? and efficiency at various supply voltage frequencies. It is shown that ???????????????? at all supply voltage frequencies remains very high, while the efficiency is extremely low. The main way to increase the engine efficiency is to increase the frequency of its supply voltage as much as possible. It is proposed to extend the results obtained to other possible industrial applications of linear electric drives.